The ArcAB two-component system is associated with the susceptibility of Aggregatibacter actinomycetemcomitans to superoxide and hydrogen peroxide - Mohammad Farid Ratman; Yuichi Oogai; Airi Matsumoto; Masanobu Nakata (mSphere)
ABSTRACT Aggregatibacter actinomycetemcomitans is a Gram-negative facultative anaerobe and is associated with periodontal disease. This bacterium is exposed to environmental stresses, such as osmotic pressure, temperature shifts, pH shifts, and antimicrobial substances, including reactive oxygen species (ROS), in the human oral cavity. The bacterial two-component system ArcAB modulates gene expression in response to environmental changes, primarily by sensing oxygen pressure in several pathogens belonging to the γ-proteobacteria. It is also known to provide adaptation to ROS stress; however, its function in A. actinomycetemcomitans remains unclear. In this study, we found that the expression of sod, which encodes superoxide dismutase, was increased in the inactivated mutant of arcA, which encodes a response regulator. The mutant exhibited reduced susceptibility to superoxide and hydrogen peroxide (H2O2). Additionally, this strain showed reduced susceptibility to H2O2 from Streptococcus sanguinis and increased survival in macrophages. Since ArcB is the cognate histidine kinase of ArcA, the inactivated mutant of arcB was analyzed for its phenotypes. The arcB mutant exhibited reduced susceptibility to superoxide and H2O2. Compared to wild type, the phosphorylation level of ArcA in the arcB mutant was decreased. These results suggest that the ArcA response regulator receives phosphate groups from ArcB histidine kinase and negatively regulates the expression of sod, thereby affecting bacterial survival in response to ROS produced by oral commensals and host immune cells.IMPORTANCEAggregatibacter actinomycetemcomitans is an oral pathogen that is known to be a highly virulent periodontal pathogen, showing strong adherence to periodontal tissue and toxin production, which leads to aggressive periodontitis. This bacterium is associated not only with oral infections but also with systemic infections, such as infective endocarditis and brain abscesses. Therefore, elucidating the adaptation mechanisms of this bacterium is important for human health. Bacterial two-component systems (TCSs) have been studied as attractive targets for elucidating bacterial fitness and pathogenicity in the host. This study characterized a TCS in A. actinomycetemcomitans, ArcAB, which is associated with susceptibility to ROS produced by host cells or oral commensals. Our findings provide insights into the bacterial adaptation mechanism against oxidative stress, which is crucial for understanding the survival strategies of the periodontal pathogen.